Implementasi Metode WMA, SMA, dan DES Dalam menentukan Jumlah Stok - Muhammad Aldy Fadhli Robby; Rina Candra Noor Santi (Elkom : Jurnal Elektronika dan Komputer, 2022)
Pusattinta.com Store is engaged in selling printer ink. The problem faced is difficult to determine the amount of stock to meet customer needs and not cause accumulation of goods for a long time. With the above problems, a forecasting application was made using the Java programming language with the WMA, SMA, and DES methods. The WMA method is assigned a different weight for each available past historical data, SMA is a value smoothing forecasting method by taking a group of observed values ​​and looking for the average, DES processes smoothing twice. Where each data is given a weight symbol. The magnitude of is 0 to 1. From the 3 methods, it is known that the average MSE of each method is WMA : 102,898.57, SMA : 89,579,446 and DES : 87,156,989. The method with the smallest MSE average is the most appropriate method to use.